2003
DOI: 10.1110/ps.0235703
|View full text |Cite
|
Sign up to set email alerts
|

Roles of conformational stability and colloidal stability in the aggregation of recombinant human granulocyte colony‐stimulating factor

Abstract: We studied the non-native aggregation of recombinant human granulocyte stimulating factor (rhGCSF) in solution conditions where native rhGCSF is both conformationally stable compared to its unfolded state and at concentrations well below its solubility limit. Aggregation of rhGCSF first involves the perturbation of its native structure to form a structurally expanded transition state, followed by assembly process to form an irreversible aggregate. The energy barriers of the two steps are reflected in the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
324
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(340 citation statements)
references
References 40 publications
14
324
2
Order By: Relevance
“…Although the exact mechanism was hard to define, this complex mechanism with zeolite treatments might have resulted proteins to possess anisotropic charge distribution on their surfaces and this might have caused increase in dipoles. Thus protein-protein interactions might be attractive and lead aggregation to be energetically favorable [39,40].…”
Section: Characterization Resultsmentioning
confidence: 99%
“…Although the exact mechanism was hard to define, this complex mechanism with zeolite treatments might have resulted proteins to possess anisotropic charge distribution on their surfaces and this might have caused increase in dipoles. Thus protein-protein interactions might be attractive and lead aggregation to be energetically favorable [39,40].…”
Section: Characterization Resultsmentioning
confidence: 99%
“…The percent of aggregate was only 7%. Previous studies (10,11) relating to the aggregation of filgrastim reported that under the same aggregation conditions filgrastim was aggregated readily with 96% loss of monomer.…”
Section: Results and Discusionmentioning
confidence: 85%
“…gregation is rapidly emerging as a key issue underlying multiple deleterious effects for protein-based therapeutics, including loss of efficacy and immunogenicity (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SIC allows rapid determination of B 22 under high throughput conditions using automated systems. A recent study [103] has presented a high-throughput self interaction chromatography application combined with chemometry (ANN: artifical is an indicator for physical protein stability (see Figure 10) [9,105,106].…”
Section: Physical Protein Stability Via Stirring Stressmentioning
confidence: 99%